Kant on the Feeling of Certainty - Mileti Nardo, Lorenzo (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This paper explores Kant’s account of certainty, examining whether – and to what extent – it can be interpreted as a feeling of the human soul in his philosophy. I argue that, for Kant, certainty can be understood as a feeling only if it is properly framed within his epistemology of assent. To support this claim, I analyze Kant’s engagement with two key figures of the German Enlightenment – Georg Friedrich Meier and Christian August Crusius – who influenced his early reflections on certainty. After outlining Meier’s and Crusius’ views, I show how Kant develops his own epistemic account of certainty, broadly identifying it with the necessity of holding-to-be-true. According to Kant, certainty must be understood in two distinct but related ways: as the expression of the highest epistemic status of our beliefs and as the feeling of conviction that accompanies the act of truth-acceptance. This dual understanding of certainty not only clarifies the peculiarities of Kant’s position in relation to his predecessors but also sheds light on key interpretative issues within his epistemic theory of assent.